2022
DOI: 10.3390/metabo12070666
|View full text |Cite
|
Sign up to set email alerts
|

Human In Vivo Metabolism and Elimination Behavior of Micro-Dosed Selective Androgen Receptor Modulator RAD140 for Doping Control Purposes

Abstract: RAD140 is a selective androgen receptor modulator which has been abused in sporting competitions. Its use is prohibited by the World Anti-Doping Agency (WADA) for athletes at all times. In addition to its illicit use, adverse analytical findings of RAD140 in doping control samples might result from other scenarios, e.g., the ingestion of contaminated dietary supplements. The differentiation between samples resulting from such contamination scenarios and intentional doping presents a considerable challenge, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The mechanism underlying proposed anabolic steroid-induced rhabdomyolysis is unknown, and the causality is not fully established. However, SARMs have many metabolites and high potential for off-target effects [ 35 , 59 , 60 , 61 , 62 ]. Furthermore, it is rational to hypothesize that individuals starting a workout supplement may perform more strenuous activity if the individual believes that the supplement will enhance performance.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying proposed anabolic steroid-induced rhabdomyolysis is unknown, and the causality is not fully established. However, SARMs have many metabolites and high potential for off-target effects [ 35 , 59 , 60 , 61 , 62 ]. Furthermore, it is rational to hypothesize that individuals starting a workout supplement may perform more strenuous activity if the individual believes that the supplement will enhance performance.…”
Section: Discussionmentioning
confidence: 99%
“…There is no need for a transfer of a large dose of doping agent. In addition to what has been published 15 about ostarine (detection for several days in urine of a single 1 µg oral dose), other studies have confirmed that a single 1 µg dose of ligandrol 16 or RAD140 17 are detectable over several days in urine. The pharmacologically active doses of these oral selective androgen receptor modulators, controlled under section S1.2 (other anabolic agents) by the World Anti-Doping Agency (WADA) are in the range 10 to 30 mg per day.…”
mentioning
confidence: 71%
“…However, I am not aware of any report dealing with drug consumption by subject 1 and subsequent urine measurement in subject 2 after kissing or sexual relationship. Nevertheless, administration of drugs in a micro-dose of 1−10 µg, [15][16][17] which obviously can be in the range of what is present in oral fluid or semen, has resulted in detectable amounts in urine for several days. This also allows the crossing of "possible" to "probable" for drug transfer during intimate moments.…”
mentioning
confidence: 99%
“…In order to provide additional data into elimination profiles of frequently observed SARMs, LGD-4033 and RAD140 (Figure 1, 2 and 4) were each administered to five male volunteers in single and multiple microdoses of 1, 10, and 50 μg, and urine was collected up to 47 days after administration. 50,51 The studies aimed at mimicking scenarios of contamination, where individuals (e.g., athletes) are exposed to low amounts of prohibited substances and how such an exposure is Moreover, no enantiomeric depletion was observed, in contrast to reports published for clenbuterol contamination scenarios 53,54 and urinary elimination profiles.…”
Section: Other Anabolic Agentsmentioning
confidence: 99%
“…Similarly, the interpretation of urinary SARM findings has been the subject of considerable debate in the past, with low concentrations of prohibited substances or their metabolites potentially originating from either recent contamination or past doping practices. In order to provide additional data into elimination profiles of frequently observed SARMs, LGD‐4033 and RAD140 (Figure 1, 2 and 4 ) were each administered to five male volunteers in single and multiple microdoses of 1, 10, and 50 μg, and urine was collected up to 47 days after administration 50,51 . The studies aimed at mimicking scenarios of contamination, where individuals (e.g., athletes) are exposed to low amounts of prohibited substances and how such an exposure is traceable in urine.…”
Section: Anabolic Agentsmentioning
confidence: 99%